Sectional Analysis Procedure for Reinforced Concrete Members Subjected to Pure Torsion - Jongkwon Choi; Seong-Cheol Lee (Advances in Civil Engineering)
A sectional analysis procedure for reinforced concrete members subjected to pure torsion is presented in this paper. On the development of the analysis procedure, the reinforced concrete section is modeled with reinforced concrete elements subjected to biaxial stress states, on the basis of the thin-walled tube analogy. Each reinforced concrete element is analyzed with the modified compression field theory (MCFT) to take into account for compression softening and tension stiffening effects in cracked reinforced concrete. Considering analysis results of reinforced concrete elements, equilibrium, and compatibility on the section are checked. For verification of the developed analysis procedure, analytical predictions were compared with test results of 16 reinforced concrete beams subjected to a pure torsional load which are available in the literature. Comparison between predicted and experimentally obtained torque-twist responses showed that the proposed procedure is capable of capturing the ultimate torsional capacity as well as the angle of twist within a reasonable range.